Carbon footprint assessment within the Romanian manufacturing sector - Blagu, Diana; Szabo, Denisa; Dragomir, Mihai (Technium Social Sciences Journal, 2021)
The paper presents the results of a survey performed upon 83 Romanian companies, most of them in the manufacturing sector, with respect to their preoccupations and initiatives related to sustainability, and especially becoming active players in envisioned the low carbon economy. We conclude that there are promising signs of change and that continued support is needed in the future for companies to undergo the needed transformations to their processes and product development undertakings.